New Patterns of Diplomacy in the Light of Information and Communication Technology - Ameer, Aya; Abd-Baqui, Luma (Journal of Legal Sciences, 2022)
The concept of information and communication technology between countries has become a well-known concept in the international community, and in light of this diplomacy has played an important and vital role in the field of international relations, through which all matters of interest to different countries are addressed, and their common interests are reconciled as well as divergent views. In light of this, the information and communication technology revolution has become a factor whose impact cannot be overlooked on the international system and international law in general, and that this development in information and communication technology has helped facilitate relations between states and international organizations, and create new forms or methods for diplomats.